LUDIC AND AFFECTIVITY IN THE LEARNING PROCESS (Fiep Bulletin - online, 2016)
This bibliographic nature dissertation attempts to systematize the concepts of affection and playfulness in a clear and concise approach to the relationship between them and the pedagogical teacher-student, pointing to the fact that affection can determine the success or failure of a child in school. The pedagogical relationship acceptance or aversion between educator and student may interfere with the teaching and learning process and the relationship between those involved. The recreational activities (play and play) in the educational context, possible points of convergence and divergence. The playfulness is a strategy to be used as a stimulus in the construction of human knowledge and progression of different cognitive abilities. Therefore inseparable from its history and its numerous theories and stories about their pedagogical value. In psychoanalytic approach, affection is the playfulness are presented as dual required in the learning process, but so far no need to transfer without transferring the teacher connection student becomes more complex We noticed that the contribution of psychoanalysis in the educational process, is to direct students and educators understanding the importance of affection and playfulness in the educational context is valued in the transference relationship between those involved in the discovery of pleasure and desire to learn and to teach.
Keywords: Affection. Playful. Psychoanalysis. Transfer. Learning.